Candida Manassasensis Infection in Mass Mortality Case of Siberian Sturgeon Acipenser Baerii Fingerlings in the Republic of Korea: A Case Report. Issue 4 (8th October 2022) - Kim, Sang Wha; Han, Se Jin; Giri, Sib Sankar; Kim, Sang Guen; Kwon, Jun; Lee, Sung Bin; Park, Se Chang
Abstract: With the growing demand for caviar products, sturgeon (family Acipenseridae) have become some of the most popular species in the aquaculture industry. Since sturgeon need more than 10 years to become sexually mature, protection against fatal diseases becomes particularly important in the industry. In March 2018, approximately 10% of Siberian Sturgeon Acipenser baerii fingerlings in a sturgeon hatchery in Jeolla Province, Republic of Korea, exhibited anorexia, abdominal distension, buoyancy loss, and abnormal behavior and eventually showed a 90% fatality rate. Twenty moribund fish were necropsied, and a distended stomach filled with gas was found in every case. A single colony dominated the intestinal lumen smear and was identified as Candida manassasensis by polymerase chain reaction targeting 18S ribosomal RNA. The same microorganism was also detected in the sturgeons' feed. Antifungal resistance was examined using the VITEK 2 system, and the isolate was susceptible to voriconazole, caspofungin, micafungin, and flucytosine. The environmental stress factor for this case was speculated as decreased water temperature. Since similar cases have been observed for many years, further research to optimize precise treatment and prevention methods is required.